The kill order [compact disc, unabridged] - Dashner, James, 1972- (Dashner, James, 1972- Maze runner series., 2012)
Before WICKED was formed, before the Glade was built, before Thomas entered the Maze, sun flares hit the earth and mankind fell to disease.